2018
DOI: 10.1186/s12889-018-5848-0
|View full text |Cite
|
Sign up to set email alerts
|

Rango Cards, a digital game designed to promote a healthy diet: a randomized study protocol

Abstract: BackgroundSeveral food and nutrition education actions have been described in the literature, with emphasis on the recommended use of innovative methods when addressing a young audience. Digital games are an attractive, dynamic, and motivating resource for teaching and learning practices, and adolescents form the group that readily accepts and adopts new technologies. Adapting dietary and nutritional guidelines to change dietary behavior is a challenge, and game-based learning has several benefits that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 65 publications
0
12
0
8
Order By: Relevance
“…This study had no exclusion criteria. Additional sampling information has been published elsewhere (23) .…”
Section: Randomisation and Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This study had no exclusion criteria. Additional sampling information has been published elsewhere (23) .…”
Section: Randomisation and Recruitmentmentioning
confidence: 99%
“…Rango Cards is free, in Portuguese, compatible with Android and iOS devices and available from Google Play and App Store since April 2017. More information about the game can be found in Chagas et al (23) .…”
Section: Interventionmentioning
confidence: 99%
“…The images were used to address topics involving the amount of sugar and fat present in food, healthy food substitutions, and fruit and vegetable consumption [ 7 ]. For adolescents, a nutritional intervention to promote healthy dietary practices is currently under way in Brazil [ 10 ]. The intervention involves a digital card game that is installed in student-owned mobile devices where the cards, differentiated by color, represent healthy and unhealthy foods, meals, and dietary practices.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Mack et al ( 55 ) proved through the development of different serious games, that these games increase the nutritional knowledge of the player, enhancing the positive attitude toward healthy food intake and their coping ability. In the same way, Chagas et al ( 57 ) developed Helperfriend, a serious game based on behavior change techniques (BCT) to moderate physical activities, eating behavior and socio-emotional behavior. In line with previous scholars, their study confirmed the effectiveness of games in improving the dietary knowledge of the player and food intake behavior.…”
Section: Discussionmentioning
confidence: 99%